Caracterização estrutural e funcional de uma xiloglucanase de Xanthomonas campestris - Araújo, Evandro Ares de (Universidade Federal de São Carlos, 2013)
Xyloglucanases (Xghs) are important enzymes involved in xyloglucan modification and degradation. Xanthomonas campestris (Xcc) is a phytopathogenic bacterium which produces a large number of glycosyl hydrolases (GH), but has only one family 74 GH (Xcc-Xgh). A Xcc-Xgh xyloglucan-specific endo-β-1,4-glucanase from family GH74 has been cloned from the Xanthomonas campestris by expression cloning in E. coli. The recombinant enzyme was purified by resin another Ni-NTA column and gel permeation chromatography. The recombinant Xcc-Xgh is stable at pH of 5.3 and temperature below 40°C; the specific activity this enzyme were determined such as 9.31U/mg protein. This enzyme was purified and crystallized. Diffraction datasets were collected for native enzyme and its two complexs with glucose at maximum resolution of 2.0, 2.1 and 2.7 Å, respectively. Data were indexed in the hexagonal crystalline system with unit-cell parameters a=b=153.4 and c=84.9 Å. Data scaling indicated that crystals belong to either space group P61 or its enantiomorph P65. Translation search in molecular replacement calculations solved the space group ambiguity (P61) and the structure refinement is currently in progress. That elucidation of the three-dimensional structure by SAXS and Crystallography of this enzyme will increase our understanding of structure function relationships of the GH74 family members and might provide new structural insights about xyloglucanases mode of action on xyloglucan polysaccharides.
Structural and functional characterization of a xyloglucanase from Xanthomonas campestris
Keywords: Biotecnologia; Enzimas; Bactérias; Xiloglucanases; Xanthomonas campestris; Enzyme; OUTROS